Penser le Nouveau Monde - Pierre Prétou (Cahiers des Amériques Latines)
The persistence of medieval representations of the world in the sixteenth century puts into perspective the significance of the experience of oceanic navigators. Where a regressive understanding of history sees in the emergence of modern cartography the demise of a system of thought, it does not account for the persistence of a vision of space inherited from the Christian Middle Age; the very vision which had led to the Great Discoveries. Neither dead nor outdated or even contested, medieval cosmography was rejuvenated at the sources of Mundus Novus. Imago Mundi adapted to, regenerated and triumphed over the new circumstances. From Colon to Las Casas, the Garden of Eden was physically present and its disappearance from the field of knowledge resulted from the transformations of European religiosity; more so than it resulted from the chronology of the exploration of the Americas. Until the mid-sixteenth century, the knowledge of the world was not going through a transitory phase thank to the invention of the oceanic and American worlds but was rather validated.